Longitudinal evaluation of patient-reported outcomes measurement information systems measures in pediatric chronic pain. Issue 2 (February 2016) - Kashikar-Zuck, Susmita; Carle, Adam; Barnett, Kimberly; Goldschneider, Kenneth R.; Sherry, David D.; Mara, Constance A.; Cunningham, Natoshia; Farrell, Jennifer; Tress, Jenna; DeWitt, Esi Morgan
Abstract : Abstract: The Patient-Reported Outcomes Measurement Information System (PROMIS) initiative is a comprehensive strategy by the National Institutes of Health to support the development and validation of precise instruments to assess self-reported health domains across healthy and disease-specific populations. Much progress has been made in instrument development, but there remains a gap in the validation of PROMIS measures for pediatric chronic pain. The purpose of this study was to investigate the construct validity and responsiveness to change of 7 PROMIS domains for the assessment of children (ages: 8-18) with chronic pain—Pain Interference, Fatigue, Anxiety, Depression, Mobility, Upper Extremity Function, and Peer Relationships. The PROMIS measures were administered at the initial visit and 2 follow-up visits at an outpatient chronic pain clinic (CPC; N = 82) and at an intensive amplified musculoskeletal pain day-treatment program (N = 63). Aim 1 examined construct validity of PROMIS measures by comparing them with corresponding "legacy" measures administered as part of usual care in the CPC sample. Aim 2 examined sensitivity to change in both CPC and amplified musculoskeletal pain samples. Longitudinal growth models showed that PROMIS' Pain Interference, Anxiety, Depression, Mobility, Upper Extremity, and Peer Relationship measures and legacy instruments generally performed similarly with slightly steeper slopes of improvement in legacy measures. All 7 PROMIS domains showed responsiveness to change. Results offered initial support for the validity of PROMIS measures in pediatric chronic pain. Further validation with larger and more diverse pediatric pain samples and additional legacy measures would broaden the scope of use of PROMIS in clinical research. Abstract : Initial evidence for construct validity and responsiveness to change was found for Patient-Reported Outcomes Measurement Information System pediatric short-form measures in youth with chronic pain.